A recurrent mutation, ala391glu, in the transmembrane region of FGFR3 causes Crouzon syndrome and acanthosis nigricans. Issue 9 (September 1996) - Wilkes, D; Rutland, P; Pulleyn, L J; Reardon, W; Moss, C; Ellis, J P; Winter, R M; Malcolm, S
Abstract : Mutations in the fibroblast growth factor receptor 2 (FGFR2) gene have previously been identified in Crouzon syndrome, an autosomal dominant condition involving premature fusion of the cranial sutures. Several different missense and other mutations have been identified in Crouzon syndrome patients, clustering around the third immunoglobulin-like domain. We report here the identification of a mutation in the transmembrane region of FGFR3, common to three unrelated patients with classical Crouzon syndrome and acanthosis nigricans, a dermatological condition associated with thickening and abnormal pigmentation of the skin. The mutation within the FGFR3 transcript was determined by direct sequencing as a specific gcg to gag transversion, resulting in an amino acid substitution ala391glu within the transmembrane region.